Dialog Antar Agama di Era Digital: Analisis Podcast "Berbeda Tapi Bersama" Habib Husein Ja'far Al-Hadar - Asna, Ni'am Khurotul; Syahriyah, Ummi Ulfatus (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This article aims to analyse the study of religious tolerance presented on Habib Husein Ja’far al-Hadar’s podcast channel. In the digital era, preachers are challenged to package the content they deliver in engaging ways while addressing various circulating issues. The podcast hosted by Habib Husein Ja’far al-Hadar discusses light yet substantive explanations regarding the religious practices of Indonesian society. Religion and indigenous beliefs in Indonesia are explored through conversational, dialogic, and humorous discussions between two speakers. This study uses a qualitative research method with content analysis as its primary analytical approach. To strengthen the research, the author also employs library research by reviewing various relevant literature. The primary data source of this research is Habib Ja’far al-Hadar’s podcast channel, supported by books and scholarly articles related to the theme of religious tolerance. The findings indicate that several episodes of the Noice podcast “Berbeda Tapi Bersama” reveal crucial points for the future of tolerance in Indonesia. The author identifies several indications, including that each religion offers exemplary teachings and encourages respect for the principles and rules of other religions. Each religion has points of convergence and similarities, even if its intentions and values differ. These elements demonstrate strong respect and tolerance, with dialogue serving as a key foundation for sustaining diversity.